Stimulation of ipt overexpression as a tool to elucidate the role of cytokinins in high temperature responses of Arabidopsis thaliana - Skalák, Jan; Černý, Martin; Jedelský, Petr; Dobrá, Jana; Ge, Eva; Novák, Jan; Hronková, Marie; Dobrev, Petre; Vanková, Radomira; Brzobohatý, Břetislav (Journal of experimental botany, 2016)
Cytokinins (CKs) are phytohormones regulating plant growth and development as well as response to the environment. In order to evaluate their function in heat stress (HS) responses, the effect of CK elevation was determined during three types of HS - targeted to shoots, targeted to roots and applied to the whole plant. The early (30min) and longer term (3h) responses were followed at the hormonal, transcriptomic and proteomic levels in Arabidopsis transformants with dexamethasone-inducible expression of the CK biosynthetic gene isopentenyltransferase (ipt) and the corresponding wild-type (Col-0). Combination of hormonal and phenotypic analyses showed transient up-regulation of the CK/abscisic acid ratio, which controls stomatal aperture, to be more pronounced in the transformant. HS responses of the root proteome and Rubisco-immunodepleted leaf proteome were followed using 2-D gel electrophoresis and MALDI-TOF/TOF. More than 100 HS-responsive proteins were detected, most of them being modulated by CK increase. Proteome and transcriptome analyses demonstrated that CKs have longer term positive effects on the stress-related proteins and transcripts, as well as on the photosynthesis-related ones. Transient accumulation of CKs and stimulation of their signal transduction in tissue(s) not exposed to HS indicate that they are involved in plant stress responses.
Keywords: Plant Shoots; reakce na tepelný šok; dexamethason; heat stress; Arabidopsis thaliana; Abscisic Acid; Arabidopsis; výhonky rostlin; Plant Roots; signální transdukce; regulátory růstu rostlin; Dexamethasone; stanovení celkové genové exprese; Cytokinins; regulace genové exprese u rostlin; Signal Transduction; proteome.; kořeny rostlin; Gene Expression Profiling; proteomika; cytokininy; Abscisic acid; Plant Growth Regulators; cytokinin; Gene Expression Regulation, Plant; Heat-Shock Response; vysoká teplota; spektrometrie hmotnostní - ionizace laserem za účasti matrice; isopentenyltransferase; Alkyl and Aryl Transferases; Proteomics; Hot Temperature; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; kyselina abscisová; alkyltransferasy a aryltransferasy